PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IVA SD NEGERI 165 PEKANBARU - Juita, Masri Ratna; Kurniaman, Otang; Witri, Gustimal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Background problem in this research is the lack of science student learning outcomes, which can be seen in students' grades. The research was conducted in Pekanbaru. In the second semester of the 2015/2016 Academic Year. With this research subject is class IV A SDN 165 Pekanbaru by the number of students 37 people. The number of students who do not reach KKM many as 16 people with a percentage of 43.24%, while the number of students who reached the KKM many as 21 people with a percentage of 56.75% with the average - average grade 65.45. KKM has been established in schools, 73. According to this problem, this research uses classroom action research by applying direct instructional model. The learning result obtained from UH before action with value - average rose 65.45 at UH I cycle I with value - average into 76.62 (17.06% increase). At UH II increases the value - average 81.08 (23.88% increase). Individually completeness of the original base score 21 increases in the first cycle were 28 people and the second cycle increased to 32 people. Classical completeness on the basis of the percentage score of 56.75% with a category is not finished, the second cycle of 75.67% with a category is not exhaustive, and the second cycle increased to 86.49% with the category completely. The application of direct learning model can improve the performance of teachers, so as to improve learning outcomes IPA A fourth grade students of SDN 165 Pekanbaru.Â Keywords: Direct Learning Model, Learning Outcomes IPA